2014
DOI: 10.5433/1679-0359.2014v35n4suplp2817
|View full text |Cite
|
Sign up to set email alerts
|

Methods of feed restriction for molt induction in commercial laying hens

Abstract: An experiment was carried out to evaluate methods of quantitative or qualitative feed restriction for inducing molt on the performance of Hy -Line Brown layers in the second lay cycle. Two hundred and twenty -five birds with 88 wks-old Hy -Line Brown were used in a completely randomized design with five treatments: Quant 100 -restriction of 100% of the daily amount recommended by lineage manual; Quant 75 -restriction of 75% of the daily amount recommended; Quant 50 -restriction of 50% of the daily amount recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The birds weighed 2.072 g ± 137 g at the beginning and 1.501 g ± 126 g at the end of the fasting period, resulting in a mean weight reduction of 27.7%. This reduction indicated that the fasting to which the birds were subjected was successful, as recommended by CERBARO et al (2014).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The birds weighed 2.072 g ± 137 g at the beginning and 1.501 g ± 126 g at the end of the fasting period, resulting in a mean weight reduction of 27.7%. This reduction indicated that the fasting to which the birds were subjected was successful, as recommended by CERBARO et al (2014).…”
Section: Resultsmentioning
confidence: 91%
“…During fasting, egg production is temporarily interrupted, allowing the reproductive system to rest and the bird to prepare for a new cycle of egg production (LEE, 1982). This procedure is considered highly stressful (HOSHINO et al, 1988;KOELKEBECK & ANDERSON, 2007), and some alternative protocols have been tested, to maintain the welfare of the birds by reducing the stress (BOZKURT et al, 2016;CERBARO et al, 2014;GONGRUTTANANUN et al, 2013). However, no studies have jointly tested the methods applied to evaluate the physiological stress arising from feed restriction in commercial laying hens.…”
Section: Introductionmentioning
confidence: 99%